Effect of pharmacological preconditioning with sevoflurane during hepatectomy with intermittent portal triad clamping. Issue 9 (September 2019) - Nguyen, Truong Minh; Fleyfel, Maher; Boleslawski, Emmanuel; M'Ba, Léna; Geniez, Marie; Ethgen, Sabine; Béhal, Hélène; Lebuffe, Gilles
Abstract: Background: During hepatectomy, intermittent portal triad clamping (IPC) reduces ischemia-reperfusion injuries. Pharmacological preconditioning with sevoflurane revealed similar properties. The aim of the study was to evaluate the combination of a sevoflurane preconditioning regimen with IPC on ischemia-reperfusion injuries. Methods: Three regimens of anesthesia were applied: group SEV with continuous application of sevoflurane, group PRO with continuous propofol infusion and group PC where continuous propofol was substituted by sevoflurane (adjusted to reach MAC∗1.5) for 15 min before IPC. Endpoints were the values of AST and ALT, factor V, prothrombin time, bilirubinemia over the 5-postoperative days (POD), morbidity and mortality at POD30 and POD90. Results: The ALT values at POD5 were lower in the PC group (n = 27) 74 (48 –98) IU/L compared to PRO (n = 26) and SEV (n = 67) respectively 110 (75 –152) and 100 (64 –168) IU/L (p = 0.038). The variation of factor V compared to preoperative values was less important in the PC and SEV groups respectively −14% and −16% vs −30% (PRO) (p = 0.047). Conclusion: Our study suggests that sevoflurane attenuates ischemia-reperfusion injuries on liver function, compared to propofol, without benefit for a specific regimen of pharmacological preconditioning when IPC is applied.